Preparation and study of the optical properties of a detector (Cu-Si) photocatalyst (Journal of the College of Basic Education, 2022)
In this research, a metal-semi-conductor contact photodetector was prepared using the vacuum thermal evaporation method to evaporate pure copper metal on the smooth face of type (n) silicon slices and pure aluminum metal on the rough face of these slices with a thickness of (100 Ao) and for both sides after using Chemical etching method for cleaning silicon slides. The samples were annealed in a convection oven in the presence of nitrogen at a temperature of (673 K) for 15 minutes. The photocurrent relationship, spectral response, noise equivalent power, quantitative efficiency and quantitative quantitative efficiency of the prepared detector with the incident wavelength at room temperature were studied to determine the best spectral region in which this detector can operate and the possibility of using it in suitable electronic applications.